Pelatihan Ibu-ibu Perwiritan dalam Penggunaan Aplikasi English for Kids untuk Belajar Bahasa Inggris Anak Usia Dini - Yoni Rahayu; Soraya Grabiella Dinamika; Muhammad Muslim Nasution (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service (PKM) activity is carried out to disseminate useful knowledge related to the use of the application (English for Kids) to learn English for early childhood for Perwiritan women. The method of implementing this PKM is carried out with participation, partnership, networking, and process-oriented which includes socialization, demonstration, teaching, explaining, and direct practice. Participants in this activity amounted to 25 people, who were mothers of Mulia Asri Residence, Dusun IIb, Klambir Lima Kampung, Hamparan Perak District, Deli Serdang Regency. The results of the activity were obtained through direct observation. The results and targets achieved in this service activity are to provide knowledge to parents, especially housewives, about the English for Kids application which can help early childhood in acquiring and learning English vocabulary in a fun way through smartphones. Thus, this activity has made a real contribution to developing children's potential to acquire English vocabulary with the assistance of mothers at home in its implementation. The questionnaire test results from the pre-test and post-test showed an N-gain result of 0.83, categorized as a high gain (g > 0.7).  So, the participants' understanding and knowledge of the benefits and uses of the English for Kids application have increased.